Prevalence of and risk factors for human rhinovirus infection in healthy aboriginal and non-aboriginal western australian children - Annamalay, A.; Khoo, S.; Jacoby, P.; Bizzintino, J.; Zhang, Guicheng; Chidlow, G.; Lee, W.; Moore, H.; Harnett, G.; Smith, D.; Gern, J.; Lesouef, P.; et al. (2012)
Background: Human rhinovirus (HRV) species C (HRV-C) have been associated with frequent and severe acute lower respiratory infections and asthma in hospitalized children. The prevalence of HRV-C among healthy children and whether this varies with ethnicity is unknown. Objective: To describe the prevalence of HRV species and their associations with demographic, environmental and socioeconomic factors in healthy Aboriginal and non-Aboriginal children. Methods: Respiratory viruses and bacteria were identified in 1006 nasopharyngeal aspirates collected from a cohort of 79 Aboriginal and 88 non-Aboriginal Western Australian children before 2 years of age. HRV-positive nasopharyngeal aspirates were typed for HRV species and genotypes. Longitudinal growth models incorporating generalized estimating equations were used to investigate associations between HRV species and potential risk factors. Results: Of the 159 typed specimens, we identified 83 (52.2%) human rhinovirus species A (HRV-A), 26 (16.4%), human rhinovirus species B and 50 (31.4%) HRV-C. HRV-C was associated with upper respiratory symptoms in Aboriginal (odds ratio, 3.77; 95% confidence interval:1.05-13.55) and non-Aboriginal children (odds ratio, 5.85; 95% confidence interval: 2.33-14.66). HRV-A and HRV-C were associated with carriage of respiratory bacteria. In Aboriginal children, HRV-A was more common in the summer and in those whose mothers were employed prior to delivery. In non-Aboriginal children, day-care attendance and exclusive breast-feeding at age 6-8 weeks were associated with detection of HRV-A, and gestational smoking with detection of HRV-C. Conclusions: Factors associated with the presence of HRV differ between Aboriginal and non-Aboriginal children. In contrast to HRV-A, HRV-C is associated with upper respiratory symptoms suggesting that HRV-C is likely to be implicated in respiratory illness. © 2012 by Lippincott Williams ? Wilkins.